A dynamic perspective on subsidiary autonomy - Ambos, Björn; Asakawa, Kazuhiro; Ambos, Tina C. (Global strategy journal, 2011)
Prior investigations treated subsidiary autonomy more or less as a static concept, but the headquarters‐subsidiary relationship is likely to evolve and result in changing power positions over time. This article examines the static and dynamic impacts of external/internal embeddedness on the autonomy of overseas R&D subsidiaries. Based on data from 73 overseas R&D subsidiaries of German firms, we show that a dynamic perspective indeed produces counterintuitive results, namely that high internal embeddedness in the past may help laboratories gain higher levels of autonomy in the future, whereas high external embeddedness may lead to lower levels of autonomy in the future. Our results indicate that building trust and linking up with headquarters are important strategies for subsidiaries wishing to be granted autonomy in the future.